Inhibitory effect of N–ethylmaleimide in two types of glutathione reductases - Nýdlová, Erika; Roušar, Tomáš (University of Pardubice, 2012)
Glutathione reductase (GR) is a key enzyme of glutathione metabolism. This enzyme catalyzes the NADPH-dependent reduction of glutathione disulfide to a reduced form. The aim of the described study was to estimate an enzyme inhibition in two types of glutathione reductases (human and yeast) through Nethylmaleimide (NEM). The glutathione reductase activity was determined by the spectrophotometric method based on the measurement of an absorbance decline (λ = 340 nm) due to oxidation of NADPH. Interestingly, it was found that the presence of 100 :M NEM had no effect in the two glutathione reductases. The inhibitory effect was proved in higher concentrations of N-ethylmaleimide; however, neither 2 mM NEM was able to diminish GR activity. The enzyme activity was reduced in both GRs; the human GR was inhibited by 15 % and 37 % in the presence of 1 mM and 2 mM NEM, respectively; the yeast GR was inhibited at the same concentrations of N-ethylmaleimide by 16 % and 35 %, respectively. We assessed NEM-induced inhibition of the enzyme activity in the presence of 1 mM GSSG (glutathione disulfide) where both GRs were inhibited to a larger extent than in 9 mM GSSG. On the other hand, if glutathione reductase was incubated with NADPH, followed by addition of NEM, the enzyme activity disappeared to a much higher extent. After 2 minutes of incubation with NADPH, the activity of yeast glutathione reductase was inhibited by 70 % and 100 % in the presence of 0.1 mM and 1 mM NEM, respectively.